Face detection and authentication - Wang, Wei. (2008)
Automatic human face detection has always been a critical part of systems that require user visual interactions, especially face recognition systems. It has drawn great attention in the field of computer vision and image processing. In this thesis, we present a fast and reliable face detection system using generalized symmetry map and Support Vector Machines to tackle the most difficult case in face detection, that is, detecting faces in a gray scale image without using color and/or motion information.